High energy microwave weapon - еlectromagnetic bomb - Banjac, Goran M.; Đorđević, Vladimir D.; Živković, Miladin Z.; Ferdjali, Abdellah (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Technological progress has led to the actualization of the problem of construction and use of high-energy microwave weapons, especially electromagnetic bombs. However, in the recent military-professional literature, this issue is little represented.Methods: The available existing literature on the subject was analyzed.Results: It has been established that the general principles of functioning and theoretical bases have been widely available and known for many years. Numerous experiments in specialized institutions have confirmed the electromagnetic pulse effectiveness. This is especially true of sensitivity of devices based on semiconductor technology. Also, it is assumed that, at the current technological level, technical solutions are widely available to a large number of entities. The most common model of electromagnetic bomb dealt with in the literature is the realization of the use of a compression flux generator and an oscillator with a virtual cathode. According to the authors, this variant would ensure that the final product has realistic physical dimensions and sufficient strength to be useful. Another problem identified in the literature is the massive absence of adequate protection measures against the effects of electromagnetic pulses. This applies not only to the civilian but also to the military sector and imposes the need to invest significant resources in order to subsequently increase resilience.Conclusion: The available literature indicates that it is possible to make an electromagnetic bomb of acceptable physical dimensions and power. It is assumed that it would generate an electromagnetic pulse with a power of about 10 GW and a frequency of 5 GHz. In combination with high-precision weapons, even protected devices would be successfully disabled. The wide presence of semiconductor technology in all spheres of life makes this weapon extremely effective and it is realistic to expect its much wider application in the coming period.
Keywords: high energy microwave weapon; electromagnetic bomb; electromagnetic pulse; explosively pumped flux compression generators; vircator